Lutas, vivências e afetos: perspectivas da família para a pessoa público-alvo da Educação Especial - Reis, Jéssica Sousa (Universidade Federal do Tocantins, 2021)
The present work has as main objective to analyze the perspectives of families that have children Target audience of Special Education - PAEE, their struggles, experiences and affections. Result of a research of qualitative approach developed under Case Study and Bibliographic method, in the city of Tocantinópolis-TO. The analysis turned in an exploratory way, about the experiences, conviviality and struggles of the six families interviewed. Divided into two axes: the first on struggles, experiences and affections, and the second focused on the educational process. It was found that there is an exacerbated protection on the part of families. This work tends to contribute to the way in which the family faces its reality and how outsiders can see the struggles, experiences and affections of these families before judging them or demanding anything. Thus, it is expected to improve communication and care for PAEE people, both for the community and for people in academic training who will have to care for and educate these people in the future.